2023
DOI: 10.1001/jamasurg.2023.1571
|View full text |Cite
|
Sign up to set email alerts
|

Rates of National Institutes of Health Funding for Surgeon-Scientists, 1995-2020

Abstract: ImportanceSurgeon-scientists are uniquely positioned to facilitate translation between the laboratory and clinical settings to drive innovation in patient care. However, surgeon-scientists face many challenges in pursuing research, such as increasing clinical demands that affect their competitiveness to apply for National Institutes of Health (NIH) funding compared with other scientists.ObjectiveTo examine how NIH funding has been awarded to surgeon-scientists over time.Design, Setting, and ParticipantsThis cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, Nguyen et al also make recommendations that attempt to “lower the bar” for surgeons, which we do not agree with. These recommendations may have adverse effects on the perception of surgeon-scientists by other scientists.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…However, Nguyen et al also make recommendations that attempt to “lower the bar” for surgeons, which we do not agree with. These recommendations may have adverse effects on the perception of surgeon-scientists by other scientists.…”
mentioning
confidence: 62%
“…In this issue of JAMA Surgery , Nguyen et al conducted a rigorous evaluation of National Institutes of Health (NIH) funding among surgical departments. They found that, from 1995 to 2000, the number of primary investigators in surgery departments increased 1.9-fold (from 968 to 1874), corresponding to an increase in the number of funding dollars by approximately 4.0-fold (from $214 million to $861 million).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many other surgical specialties report low NIH funding. 16 Despite the utility of clinical research, however, efforts should be taken to conduct more nonclinical translational and basic science research as the skull base field, and academic medicine as a whole, is moving toward a more biomechanistic-focused approach to treatment.…”
Section: Increased Academic Productivity By North American Skull Base...mentioning
confidence: 99%